Analisa Kimia Kandungan Nitrit pada Daging Burger yang Beredar di Pasar Kecamatan Duren Sawit Jakarta Timur - agustina, ika (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2016)
Nitrite preservatives commonly be used in meat which cured like a meat burger with aim for obtaining the red color which same in meat, and more recently known it can inhibits the growth of clostridium botulinum bacteria. Excessive consumption of nitrit can cause disadvantage such as poisoning and carcinogen. The method can be used to detect compounds the nitrit in meat burger that is with qualitative analysis and using sulfanilic acid reagent+ naftiletilendiamin it will form purplish red and KI reagent+HCl it will form dark blue color or violet, then the analysis quantitative method using UV-Vis spectrophotometry at a wavelength a maximum of 548 nm to determine levels of nitrite contained in meat burger. The results showed of 5 brand sempel there are 4 positive samples containing sodium nitrite and then obtained the average levels of sodium nitrite in 4 samples of meat burger brand FN of 11.7508 mg/kg, ED brand of 5.5090 mg/kg, brand VG of 5.4228 mg/kg, and brand HM of 2.5981 mg/kg showed that the levels of sodium nitrite contained in each sample does not exceed the maximum limit the use of sodium nitrit as regulations BPOM head no.36 of 2013 on the maximum limit use of materials additional food preservative that is equal to 30 mg/kg that are safe to eat. The results of the validation of analytical methods is the correlation coefficients obtained 0,997; the limit of detection and quantity 0,126 ppm and 0,421 ppm; devisiation standard 0,1557, 1.91% correlation coefficients and precision tool 98,09%.Â Keywords : sodium nitrite, meat burgers, UV-Vis Spectrophotometry, validation of analytical